Anti-hyperglycemic Effect of Psidium guajava Leaf Infusion - Rizda Nurul Zartiana; Samsudin Surialaga; Hikmat Permana (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Prevalence of diabetes mellitus is estimated to increase annually. Numerous people use traditional medicine, such as the Poidium guajava leaf to prevent this disease. This study aimed to analyse the effect of Psidium guajava leaf to inhibit glucose absorption in intestine epithelial membrane of wistar rats.Methods: This laboratory experimental study used 5 wistar rats as subjects in the Laboratory of Biochemistry at Padjadjaran University from 10−26 October 2012. All rats were given three solutions by in situ perfusionmethod. The first was 25 ml 3.0 X 10-3 M glucose solution, the second was 25 ml 3.0 X 10-3 M glucose solution with 1 ml Psidium guajava infusion added, and the third was 25 ml 3.0 X 10-3 M glucose solution.The sample from each solution was taken five times at 0, 15, 30, 45, and 60 minutes after the solutions were given. The spectrophotometer was to quantify the concentration of glucose from the samples. Data were analyzed using Friedman and Wilcoxon test.Results:The means of glucose concentration for each solution from the first solution to the third were 6.126 mg/dl, 2.447 mg/dl, and 5.345 mg/dl. The probability value showed significant difference between the first and second solutions (p ≤ 0.05).Conclusions: Psidium guajava leaf infusion can inhibit glucose absorption in wistar rat intestine and the effect is reversible. [AMJ.2015;2(4):546–9] DOI: 10.15850/amj.v2n4.508